2008
DOI: 10.3201/eid1411.071575
|View full text |Cite
|
Sign up to set email alerts
|

Mixture for Controlling Insecticide-Resistant Malaria Vectors

Abstract: The spread of resistance to pyrethroids in the major Afrotropical malaria vectors Anopheles gambiae s.s. necessitates the development of new strategies to control resistant mosquito populations. To test the effi cacy of nets treated with repellent and insecticide against susceptible and insecticideresistant An. gambiae mosquito populations, we impregnated mosquito bed nets with an insect repellent mixed with a low dose of organophosphorous insecticide and tested them in a rice-growing area near Bobo-Dioulasso,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…35 The use of synergists (e.g ., piperonyl butoxide [PBO]) to improve the efficacy of LLIN 29,36 should be further explored. Integrated approaches for malaria vector control, either by mixing two unrelated insecticides (including synergists) on the same substrates 15,25 or combining spatially different interventions within dwellings (LLIN + IRS-like treatments), also represent key options for the management of insecticide resistance in malaria-endemic areas. This later strategy is currently being investigated in south Benin through a randomized controlled trial to assess the impact of LLIN alone and in combination with CTPS on malaria incidence and transmission as well as the management of insecticide resistance of malaria vectors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 The use of synergists (e.g ., piperonyl butoxide [PBO]) to improve the efficacy of LLIN 29,36 should be further explored. Integrated approaches for malaria vector control, either by mixing two unrelated insecticides (including synergists) on the same substrates 15,25 or combining spatially different interventions within dwellings (LLIN + IRS-like treatments), also represent key options for the management of insecticide resistance in malaria-endemic areas. This later strategy is currently being investigated in south Benin through a randomized controlled trial to assess the impact of LLIN alone and in combination with CTPS on malaria incidence and transmission as well as the management of insecticide resistance of malaria vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental hut trial was carried out at the Vallée du Kou (VK7), a huge rice field area located near BoboDioulasso, Burkina Faso, 15 between October and December 2008. Both molecular M and S forms of An.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A companion study showed that these two mixtures are more efficient than conventional pyrethroid-treated nets against susceptible and resistant An. gambiae populations and did not induce any additional selective pressure on the resistance genes, Ace1 R and Kdr [15]. Criticisms on this new strategy of resistant malaria vector control focused on the short residual effect of the repellents [29].…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for Vectoclor that contained three times less cypermethrin than Cypertraz (i.e 5g/l against 15g/l). Insecticides and repellent mixtures have also been successfully used in public health against mosquitoes that present increasing levels of insecticide resistance, and this combination proved highly effective [43, 44]. This is also the case for the Vectoclor combination that has been shown to be effective against the invasive and multi resistant ticks Rhipicephalus (Boophilus) microplus [15, 45].…”
Section: Discussionmentioning
confidence: 99%